2008
DOI: 10.1189/jlb.0607392
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Advance: Eosinophils mediate early alum adjuvant-elicited B cell priming and IgM production

Abstract: Alum, aluminum-hydroxide-containing compounds, long used as adjuvants in human vaccinations, functions by ill-defined, immunostimulatory mechanisms. Antigen-free alum has been shown to act via a previously unidentified, splenic Gr1 + , IL-4-expressing myeloid cell population to stimulate early B cell priming. We demonstrate that the alum-elicited and -activated splenic myeloid cells are IL-4-expressing eosinophils that function to prime B cell responses. Eosinophils are the principal Gr1 + , IL-4 + cells in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 24 publications
5
71
0
1
Order By: Relevance
“…The results indicate that innate immune cells such as eosinophils triggered by TCS contribute to the initial IL-4 production, thus playing a critical role in initiating the Th2-type response, in favoring B cell priming and in recruiting Th2 cells to lungs as reported recently [31,40]. Our observations are consistent with the results of Jordan et al [39] and Wang et al [41]. Jordan et al found that injection of mice with alum led to the priming of spleen B cells and to the accumulation of a population of IL-4-producing Gr-1 + cells in the spleen.…”
Section: Discussionsupporting
confidence: 93%
“…The results indicate that innate immune cells such as eosinophils triggered by TCS contribute to the initial IL-4 production, thus playing a critical role in initiating the Th2-type response, in favoring B cell priming and in recruiting Th2 cells to lungs as reported recently [31,40]. Our observations are consistent with the results of Jordan et al [39] and Wang et al [41]. Jordan et al found that injection of mice with alum led to the priming of spleen B cells and to the accumulation of a population of IL-4-producing Gr-1 + cells in the spleen.…”
Section: Discussionsupporting
confidence: 93%
“…They do this, at least in part, by synthesizing and secreting a surprisingly broad spectrum of different cytokines and immune mediators [2]. In immune responses, activated eosinophils show an enhanced expression of cytokines [7][8][9]. Although activation can be induced by adjuvants alone, a stable activation is achieved only in antigen-induced immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the precipitation of antigen with aluminum hydroxide (alum) has an enhancing effect on the immune response, and alum administration has been shown to stimulate eosinophil development in the bone marrow and to promote their accumulation in the spleen [9]. In T cell-dependent immune responses, B cell activation can result in an immediate extrafollicular response to antigenic challenge, whereby antigen-activated B cells differentiate rapidly into IgM-secreting plasma cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also elicits and activates Il-4 expressing eosinophils that prime B cell responses to generate antigen-specific IgM [188]. Dysphagia (difficulty swallowing) is a common problem affecting up to 22% of patients in primary care [189], and a characteristic feature of Alzheimer's, Parkinson's and ALS.…”
Section: Asthma Dermatitis and Eosinophilic Esophagitismentioning
confidence: 99%